Deletion of FOXO1 in Chondrocytes Rescues the Effect of Diabetes on Mechanical Strength in Fracture Healing - Lu, Yongjian (Bone, 2019)
Diabetes increases the risk of fracture, impairs fracture healing and causes rapid loss of the fracture callus cartilage, which was linked to increased FOXO1 expression in chondrocytes. We recently demonstrated that deletion of FOXO1 in chondrocytes blocked the premature removal of cartilage associated with endochondral bone formation during fracture healing. However, the ultimate impact of this deletion on mechanical strength was not investigated and remains unknown. Closed fractures were induced in Col2α1.Cre(+).FOXO1(L/L) mice with lineage specific deletion of FOXO1 in chondrocytes compared to littermate controls. Type 1 diabetes was induced by multiple low dose streptozotocin treatment. Thirty-five days after fracture micro CT analysis showed that diabetes significantly reduced callus volume and bone volume (P<0.05), both which were reversed by FOXO1 deletion in chondrocytes. Diabetes significantly reduced mechanical strength measured by maximum torque, stiffness, modulus of rigidity and toughness and FOXO1 deletion in diabetic mice rescued each parameter (P<0.05). Diabetes also reduced both bone volume and mechanical strength in non-fractured femurs. However, FOXO1 deletion did not affect bone volume or strength in non-fractured bone. These results point to the important effect that diabetes has on chondrocytes and show for the first time that the premature removal of cartilage induced by FOXO1 in chondrocytes has a significant impact on the mechanical strength of the healing bone.